Smooth Cu electrodeposition for Cu(In, Ga)Se2 thin-film solar cells: Dendritic clusters elimination by Ag buffer layer. (November 2022) - Li, Bing; Zhao, Aimei; Xiang, Dongmei; Peng, Zhuo; Yuan, Yujie; Xing, Yupeng; Yao, Liyong; Bi, Jinlian; Li, Wei
Abstract: Smooth and compact Cu(In, Ga)Se2 (CIGSe) thin film is critical to prepare high-quality solar cells. However, the "dendritic" morphology of Cu tends to form on Mo leading to a nonuniform Cu distribution during the electrodeposition process, which affects the uniformity of CIGSe and device performance. In this work, Ag was used as the underlying buffer layer and Cu was electrodeposited on Ag film instead of Mo film. By adjusting deposition parameters, smooth and compact Ag layer was obtained on the Mo surface. With the Ag buffer layer, the "dendritic" Cu on Mo was successfully eliminated. The electrodeposited Ag/Cu/In/Ga metal precursors were annealed in Se-containing atmosphere at 450 °C ∼ 550 °C for 15min to prepare (Ag, Cu)(In, Ga)Se2 (ACIGSe) absorbers. Compared with the CIGSe absorber, the crystallinity of the ACIGSe absorber was improved. The V O C, J S C, FF and efficiency of ACIGSe solar cells were improved compared with CIGSe solar cells. Ultimately, an 11.73% efficiency of ACIGSe thin-film solar cells was obtained. Highlights: Ag layer was regarded as buffer layer electrodeposited between Mo and Cu layers. Dendritic clusters of Cu were eliminated with Ag buffer layer. Compared with CIGSe without Ag buffer layer, the crystallinity of CIGSe with Ag buffer layer was improved. The V O C, J S C, FF and efficiency of ACIGSe solar cell were higher than the one of CIGSe solar cell. An 11.73% efficiency of ACIGSe thin-film solar cells was obtained.